Desempenho de filtros cerâmicos na filtração de gases a altas temperaturas - Silva, Gracinda Marina Castelo da (2008)
The creation of rigorous emission and air pollution control standards has led to a growing interest in developing technologies to clean gases that not only remove pollutants efficiently but also recycle the energy produced by the process. Ceramic filters have been the most frequently utilized to separate aerosol particles in gas streams at high temperatures. The principal characteristics of ceramic filters are low pressure drop and high collection efficiency. This study presents the experimental results on the permeability and filtration efficiency for ceramic filters of different structures and compositions at high temperatures. The filters utilized in the trials were: 0.5mm thick quartz microfiber filters, seven ceramic fiber filters (A1000, B750, B1000, 1A, 2D, 3D and 5A) from 9-12 mm thick and two ceramic filters (A12 and A13) from 9-10mm thick. All the filters were circular (5-6cm diameter) and had an effective runoff area 3cm in diameter. The quartz microfiber filters had a porosity of 0.689 with a fiber diameter of around 1.1μm; the ceramic fiber filters had a porosity of 0.5 to 0.73 and a mean fiber diameter of around 5μm. The ceramic filters had a porosity of 0.62 for the A12 sample and 0.68 for the A13 sample with a mean pore diameter of 0.33 and 0.67μm, respectively. The filters were characterized by porosity (e) determined by a mercury intrusion porosimeter (Quantachrome Poremaster) and fiber diameter was captured by a scanning electron microscope (SEM) and determined by image analysis utilizing Image Proplus for Windows software. The permeability trials were performed at room and 700o C temperatures and at velocities of 0.01 to 1.8 m/s. The equipment utilized in the permeability constant trials consisted of a blower, leak detector, micromanometer (Furness Controls Ltd. FCO14), a furnace (Maitec) and a PID type temperature controller (Flyever). The particulate material utilized in the high temperature filtration tests was concentrated phosphate with a density of 2970 kg/m3 and mean diameter of 4.62mm. The density of the particulate material was determined by a helium picnometer (AccuPyc 1330, Micromeritics). The experimental system consisted of a fluidized bed aerosol generator (TSI-3400), a particle counter (Hiac/Royco Model 5230) and a test chamber inserted in the furnace. Particulates were analyzed in eight granulometric bands: 0.75; 1.5; 2.5; 3.5; 4.5; 6; 8. and 12.5mm. The filtration experiments were carried out at three levels of temperature (room, 300 and 700ºC) at a filtration velocity of 0.05m/s. For the results obtained, there was an increase in the Darcian permeability constant, k1 which elevated the temperature for ceramic filters. For all filters studied, the filtration tests demonstrated a clear dependence between filter efficiency and test temperature: lower filtration efficiency was obtained at higher gas temperatures. The probable thermal expansion of the filter structure temporarily dilated the porous channels for fluid runoff and gas property alterations changing the removal capacity of the filter. Based on the results presented, we concluded that the filters utilized in the study are viable for industrial filtration of hot gases. The correlation proposed for the quartz microfiber was a good representation of the experimental behavior of pressure drop and the efficiency of fractional collection and was a satisfactory fit at the different test temperatures.